Separation of antipyretic analgesics by open tubular capillary electrochromatography with homopolymer coatings. Issue 18 (31st July 2019) - Liu, Lili; Qiao, Juan; Zhang, Hongyi; Qi, Li
Abstract: This study developed an open‐tubular capillary electrochromatography protocol for the analysis of antipyretic analgesic drugs, which used a multifunctional homopolymer as coating. A controlled/living radical polymerization strategy was adopted to obtain poly(N‐acryloxysuccinimide) with a tunable chain‐length. The homopolymer coating enhanced the separation performance by contributing to the hydrophobic and hydrogen‐bonding interactions between the analytes and the homopolymer. The effect of polymer chain‐length and buffer pH and concentration on the separation efficiency was evaluated. In this approach, baseline separation of the three test drugs was achieved within 15 min. The repeatability of the prepared homopolymer coating was investigated, with the relative standard deviations < 2.88% observed in intra‐ and interday runs. Good linearity in the 5–800 µM range ( R 2 ≥ 0.998) demonstrates that accurate quantitative analysis of real samples was achieved. Moreover, the proposed assay was used to quantify the three drugs (aminopyrine, 4‐aminoantipyrine, and phenacetin) in urine samples, achieving recovery rates between 92.1 and 108.7%. This promising methodology may be used for the analysis of drugs in real bio‐samples and for the development of unique homopolymer coatings for open‐tubular capillary electrochromatography systems.